Leptospirosis in Nepal - N Kandel; G D Thakur; A Andjaparidze (Journal of Nepal Medical Association, 2012)
The study has demonstrated the evidence of leptospirosis infection in the country. It has also highlighted the challenges and the need of further researches on this disease, which seems to be under reported in the country.